Quality of Care in a Paediatric Intensive Care Unit of a Tertiary Care Teaching Hospital in New Delhi - Siddharth, Vijaydeep; Gupta, Shakti Kumar; Lodha, Rakesh; Satpathy, Sidhartha (Journal of Nepal Paediatric Society, 2018)
Introduction: This research aimed to study the outcome of patient care being rendered in Paediatric Intensive Care Unit (PICU) of an apex public sector teaching hospital of North India. Material and methods: A descriptive and observational study was carried out in PICU. Medical records of all admitted patients from January to June 2011 were analysed. Demographic, morbidity and mortality parameters were studied. PIM II score was calculated to assess the severity of illness. Results: In PICU, from January to June 2011, 110 patients were admitted. Almost equal number of patients got admitted in PICU through emergency ward/casualty and other inpatient areas. Of the total patients, 66% (62) were male. Mean age of the patients admitted to PICU was 4.56 years. Three fourth patients admitted in PICU required mechanical ventilation and 652 days of mechanical ventilation was given. Patient’s required mechanical ventilation on an average of 7.01 days. Almost one third, [36.61% (21)] patients were reintubated. Majority (78.7%) of the patients required oxygen support, while 72.3% (68) required vasopressor support. Prevalence of bed sore rate was 2.1%. Only 2.1% patients required readmission within 72 hours. Mean hospital and PICU length of stay was 16.82 and 8.7 days respectively. Mean PIM 2 score of patients was 14.13% (range 0.2% to 86.9%). Conclusion: 43.6% of patients died in PICU, while hospital mortality in PICU admitted patients was 47.2%. Sepsis with septic shock was the major cause of mortality followed by pulmonary haemorrhage, disseminated intravascular coagulation. Standardised mortality was calculated to be 3.09.